Visualization Tools as a Key Component in Teaching Foreign Languages - Burieva, Nilufar Gofur kizi (Miasto Przyszłości, 2023)
This article examines the use of visual aids in teaching a foreign language, since the influence of visual aids on students’ motivation when learning a foreign language is still a matter of debate. The author believes that the use of visual aids when teaching a foreign language increases efficiency and active senses, thereby facilitating and accelerating learning and inspiring students.